BS EN ISO 10893-9 AMD1. Non-destructive testing of steel tubes. Part 9. Automated ultrasonic testing for the detection of laminar imperfections in strip/plate used for the manufacture of welded steel tubes (2nd September 2019) - British Standards Institution,
No abstract available